2006
DOI: 10.1152/ajpregu.00764.2005
|View full text |Cite
|
Sign up to set email alerts
|

The role of central vasopressin receptors in the modulation of autonomic cardiovascular controls: a spectral analysis study

Abstract: Although it has been suggested that vasopressin (VP) acts within the central nervous system to modulate autonomic cardiovascular controls, the mechanisms involved are not understood. Using nonpeptide, selective V 1a, V1b, and V2 antagonists, in conscious rats, we assessed the roles of central VP receptors, under basal conditions, after the central application of exogenous VP, and after immobilization, on cardiovascular short-term variability. Equidistant sampling of blood pressure (BP) and heart rate (HR) at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Similar effects on respiration were obtained with microinjections of the excitatory transmitter L-glutamate into the PVN (Yeh et al, 1997). Also intracerebroventricular injection of VP has been shown to increase HF-BP variability (Milutinović et al, 2006). In our study, the effect of V1aR overexpression in PVN on HF-BP magnitude could reflect an increase in the alveolar surface for blood oxygenation to support the active coping strategy observed in present experiments.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar effects on respiration were obtained with microinjections of the excitatory transmitter L-glutamate into the PVN (Yeh et al, 1997). Also intracerebroventricular injection of VP has been shown to increase HF-BP variability (Milutinović et al, 2006). In our study, the effect of V1aR overexpression in PVN on HF-BP magnitude could reflect an increase in the alveolar surface for blood oxygenation to support the active coping strategy observed in present experiments.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously reported that central V1a receptors are important in the modulation of the cardiovascular response to stress (Milutinović et al, 2006;Stojičićet al, 2008;Milutinović-Smiljanić et al, 2013). Here we investigate the role of PVN V1a receptors in autonomic adjustment of the cardiovascular system to emotional stress.…”
Section: Introductionmentioning
confidence: 85%
“…Whether or not the activation of AVP-containing neurons during noxious colon distension reflects only the anxiogenic component of pain or is more directly related to the integration and processing of pain signals warrants further studies. For instance, there is evidence of cardiovascular effects of vasopressin acting in the brain as a transmitter, in addition to its well-known peripheral vasopressor actions (Milutinović et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…pharmacological doses, increases BP [58, 59] while OT was reported to do the opposite [60]. However, application of selective antagonists, peripherally and centrally, revealed that physiological concentrations of VP and OT do not modulate BP under basal physiological conditions and do not participate in the maintenance of BP under basal physiological conditions [58, 59].…”
Section: Hormonal (Peripheral) Control Of the Cardiovascular System Bmentioning
confidence: 99%
“…pharmacological doses, increases BP [58, 59] while OT was reported to do the opposite [60]. However, application of selective antagonists, peripherally and centrally, revealed that physiological concentrations of VP and OT do not modulate BP under basal physiological conditions and do not participate in the maintenance of BP under basal physiological conditions [58, 59]. However, V1aR receptor knock-out mice were reported to exhibit lower basal BP values than wild-type controls [61] while OT knock-out mice have been reported to exhibit greater basal BP and heart rate values than wild-type controls [62].…”
Section: Hormonal (Peripheral) Control Of the Cardiovascular System Bmentioning
confidence: 99%